2013
DOI: 10.1038/ijo.2013.122
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss, exercise or both and cardiometabolic risk factors in obese older adults: results of a randomized controlled trial

Abstract: Background Obesity exacerbates the age-related decline in insulin sensitivity and is associated with risk for cardiometabolic syndrome in older adults; however, the appropriate treatment for obese older adults is controversial. Objective To determine the independent and combined effects of weight loss and exercise on cardiometabolic risk factors in obese older adults. Design One-hundred-seven obese (BMI≥30 kg/m2) older (≥65 yrs) adults with physical frailty were randomized to control group, diet group, exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
112
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 46 publications
16
112
0
1
Order By: Relevance
“…Although some previous studies have alluded to a significant reduction in TNF-α and other inflammatory cytokines in response to long-term training programs (26)(27)(28), yet in line with the present study, some recent studies have reported no change in this inflammatory cytokine following long-term training program in healthy or sick obese individuals (29,30). For example, in one study, a 12-month exercise program did not lead to changes in TNF-α, adiponectin and triglyceride levels in obese subjects (31). Furthermore, findings of a recent study showed 16 weeks of rapid walking led to an increase in serum levels of TNF-α in the absence of change in IL-6 and adiponectin in obese and overweight individuals (32).…”
Section: Discussionsupporting
confidence: 62%
“…Although some previous studies have alluded to a significant reduction in TNF-α and other inflammatory cytokines in response to long-term training programs (26)(27)(28), yet in line with the present study, some recent studies have reported no change in this inflammatory cytokine following long-term training program in healthy or sick obese individuals (29,30). For example, in one study, a 12-month exercise program did not lead to changes in TNF-α, adiponectin and triglyceride levels in obese subjects (31). Furthermore, findings of a recent study showed 16 weeks of rapid walking led to an increase in serum levels of TNF-α in the absence of change in IL-6 and adiponectin in obese and overweight individuals (32).…”
Section: Discussionsupporting
confidence: 62%
“…Villareal and coworkers at Washington University evaluated diet-induced weight loss, exercise alone, and exercise with weight loss in older obese subjects in a program to reduce frailty (5, 35). The duration of the study was one year with the exercise being combined aerobic and strength training.…”
Section: Discussionmentioning
confidence: 99%
“…For further verifying the metabolic effect of aerobic exercise in obese or overweight individuals, many randomised controlled trials (RCTs) have been performed and assessed the effect of AE on blood lipid and glucose levels [17][18][19][20]. Although a previous meta-analysis has reported the effect of AE on blood lipids in overweight and obese adults [21], the controversy still exists among some recent studies [20,22,23]. Thus, we performed this updated meta-analysis to further confirm the effect of AE on levels of blood lipid and glucose indexes in obese and overweight people.…”
Section: Introductionmentioning
confidence: 98%